2019
DOI: 10.3390/molecules25010149
|View full text |Cite
|
Sign up to set email alerts
|

Design of Iodonium Salts for UV or Near-UV LEDs for Photoacid Generator and Polymerization Purposes

Abstract: Iodonium salts are well established photoacid generators, cationic photoinitiators, as well as additives commonly used in photoredox catalytic cycles. However, as a strong limitation, iodonium salts are characterized by low light absorption properties for λ > 300 nm so that these latter cannot be activated with cheap, safe, and eco-friendly near UV or even visible light emitting diodes (LEDs). To overcome this drawback, the covalent linkage of an iodonium salt to a chromophore absorbing at longer wavelength… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 65 publications
(86 reference statements)
0
38
0
Order By: Relevance
“…Over the years, a wide range of families have been designed and synthesized as efficient photoinitiators of polymerization, activable under visible light and even under low light intensity. Among these structures, naphthalimides, [40,[52][53][54][55][56][57][58][59][60][61][62] copper complexes, [63][64][65][66][67][68][69][70][71][72][73] flavones, [20,74] iron complexes, [75][76][77][78][79] iodonium salts, [80][81][82] coumarins, [83][84][85][86][87][88][89], acridine-1,8dione, [90][91] iridium complexes, [92][93][94][95][96][97]…”
Section: Figurementioning
confidence: 99%
“…Over the years, a wide range of families have been designed and synthesized as efficient photoinitiators of polymerization, activable under visible light and even under low light intensity. Among these structures, naphthalimides, [40,[52][53][54][55][56][57][58][59][60][61][62] copper complexes, [63][64][65][66][67][68][69][70][71][72][73] flavones, [20,74] iron complexes, [75][76][77][78][79] iodonium salts, [80][81][82] coumarins, [83][84][85][86][87][88][89], acridine-1,8dione, [90][91] iridium complexes, [92][93][94][95][96][97]…”
Section: Figurementioning
confidence: 99%
“…Diaryliodonium (III) salts, in which the iodine atom adopts a T-shaped form with two bound aryl moieties and a ligand (in most cases a sulfonate anion), found application in organic synthesis as versatile arylating agents and benzyne precursors [40] as well as photoacid generators (PAGs) in cationic polymerizations. [41] Such air-and moisture-stable compounds are smoothly prepared from unfunctionalized aromatics and hypervalent iodine reagents or from simple iodoarenes in combination with appropriate oxidants. [42] Ackermann and co-workers described the thermal activation (100°C in DMF) of diaryl-Scheme 9.…”
Section: Aryliodonium Saltsmentioning
confidence: 99%
“…In addition, it was pointed out that the replacement with naphthalene or a biphenyl group was not efficient in drastically red‐shifting the absorption. In contrast, a replacement with naphthalimide chromophore could shift the light absorption to near‐UV region, [ 25 ] and the modified iodonium salt could initiate polymerization at 365 nm. In another research, both chromophore (erythrosine B) and an electron donor (ethyl 4‐dimethylaminobenzoate) were linked to the iodonium salts, and the modified iodonium salts were able to initiate polymerization at 540 nm.…”
Section: Introductionmentioning
confidence: 99%
“…[20] In the polymer field, increasing photo-reactivity of iodonium salts became a major concern; researchers covalently linked chromophores to iodonium salts whereby allowing the modified products to work as mono-component photoinitiators under near UV or even visible light irradiation. [21][22][23][24][25][26] Instead of diaryl, it has been reported that one of the phenyl groups was replaced by naphthalene [24] to expand its π-conjugation system. However, the absorption is still limited to 300 nm.…”
mentioning
confidence: 99%